GUESSTIMATE: A Programming Model for Collaborative Distributed Systems - Rajan, Kaushik; Rajamani, Sriram; Yaduvanshi, Shashank (Proceedings of Programming Language Design and Implementation (PLDI 2010), 2010)
We present a new programming model Guesstimate for developing collaborative distributed systems. The model allows atomic, isolated operations that transform a system from consistent state to consistent state, and provides a shared transactional store for a collection of such operations executed by various machines in a distributed system. Guesstimate allows each machine to have a replicated copy (called "current guesstimate") of the state so that operations on shared state can be executed locally without any blocking, while also guaranteeing that eventually all machines agree on the sequence of operations executed. Thus, each operation is executed twice, once at the time of issue when it updates the guesstimated state of the issuing machine, and once when the operation is committed (atomically) to the committed state of all machines. While we expect the results of the two executions of the operation to be identical most of the time in the class of applications we study, it is possible for an operation to succeed the first time when it is executed on the guesstimated state, and fail the second time when it is committed. Guesstimate provides facilities that allow the programmer to deal with this potential discrepancy. This paper presents our programming model, its operational semantics, its realization as an API in C#, and our experience building collaborative distributed applications with this model.